Europe's Europes: mapping the conflicts of European memory. Issue 1 (2nd January 2020) - Trimçev, Rieke; Feindt, Gregor; Krawatzek, Félix; Pestel, Friedemann
ABSTRACT: Debates about 'European memory' are frequent in public and political discourse. With the fundamental challenges the European project now faces, such debates exemplify changes in what Europe means and implies politically. Drawing on a large corpus of press articles from six EU member states and employing qualitative and quantitative methods of discourse analysis, the article examines the fields and logics of conflict about the meaning of Europe between 2004 and 2016. Intimately linked to national and post-national senses of identity, these conflicts take four different forms across different national public spheres: (1) perspectives from which 'European memory' underpins seemingly consensual conceptions of Europe; (2) conflictive conceptions of Europe along an East-West divide that present different attempts of setting rules; (3) memory conflicts establishing peripheries and boundaries of Europe; (4) a global framing of 'Europe' that understands Europe as a space of competition that mobilizes triadic patterns of conflict. The fits and misfits, and the degrees of entanglement on conflicts about 'European memory' help to understand the persistent and continuous struggles over the mental maps of Europe beyond the simplistic opposition of particularism and cosmopolitanism.